Similarities in Acquired Factors Related to Postmenopausal Osteoporosis and Sarcopenia - Joonas Sirola; Heikki Kröger (Journal of Osteoporosis)
Postmenopausal population is at increased risk of musculoskeletal impairments. Sarcopenia and osteoporosis are associated with significant morbidity and social and health-care costs. These two conditions are uniquely linked with similarities in pathophysiology and diagnostic methods. Uniform diagnostic criteria for sarcopenia are still evolving. Postmenopausal sarcopenia and osteoporosis share many environmental risk- and preventive factors. Moreover, geriatric frailty syndrome may result from interaction of osteoporosis and sarcopenia and may lead to increased mortality. The present paper reviews the factors in evolution of postmenopausal sarcopenia and osteoporosis.